Efecto del extracto de las hojas de NEEM (azadirachta indica) para el control de garrapatas en perros - Párraga Quiroz, Gema Dolores (2022)
The objective of this research was to evaluate the effect of extract from neem leaves (Azadirachta indica) by steam dragging and emulsifying it O/W for the control of ticks in dogs. Forty mixed-breed dogs were used, naturally infested with ticks (Rhipicephalus sanguineus), which were randomly distributed into 4 treatment groups: Treatment 0 (Control), Amitraz was used in solution at 250 ppm; The oily extract of Neem oil was added to the other three treatments in different doses (5%, 10% and 15%). The data was analyzed by analysis of variance and comparisons of means were applied with Tukey's test at 5% significance, using Infostat statistical software (2020). It was found that regarding the percentage of mortality of ticks per treatment, there was a significant difference for all weeks (p<0.05), where for days 7 and 14, treatments T0, T2 and T3 presented the highest percentages of ticks. mortality compared to T1, while for day 21 the highest percentages of tick mortality were obtained by T0 and T3 with 82.60% and 77.70%. It is concluded that the application of the oily extract of neem (azadirachta indica) applied in dose higher than 10% can be a natural alternative for tick control in dogs.